AFRICAN COSMOLOGY: A CATALYST TO THE GROWTH OF AFRICAN INDIGENOUS CHURCHES - Ehianu, Wilson E; Awajiusuk, Finomo Julia (Asian Horizons, 2012)
The 19th century is of great significance in the religious history of Africa. This is because it was characterized by the establishment and growth of African strand of development of Christianity. They go by various names depending on the circumstances of their birth, public perception of the group or how members perceive themselves. Some common names associated with these churches include: Separatist, Ethiopian, Zionist Spiritual, Prophetic Movement, Prayer churches, Pentecostal churches, Messianic movement, Aladura and several others.1 Though these new religious movements differ widely in style, organization and attitudes, they are called indigenous churches because they, as Omoyajowo observed “began as indigenous churches founded by indigenous persons and run under indigenous leadership.